Youth Participation in farming related activities in Mahikeng local municipality, North West province South Africa - Benny Kgopolo; Usapfa Luvhengo; Christian Mzuyanda; Khuliso Ravhuhali; Joseph Nembo Lekunze5 (JOURNAL OF SCIENTIFIC COMMUNICATION (JSC), 2020)
The study assessed socio-economic factors influencing youth participation in farming related activities in Mahikeng. A multistage sampling procedure were used to sample 150 youths using a structured questionnaire and a checklist between two schools in Mahikeng local municipality. Data was captured using Excel spreadsheet and were analysed using descriptive and logistic regression model. Descriptive results showed that, the students’ age groups in the two schools ranged from 14-35 years of age. Logistic regression results revealed that factors such as lack of support, limited information about agribusiness and extension support influence youth participation in agricultural activities. The study recommends the strengthening of a relationship between youth and the local department of agriculture.